Silicon Improves Maize Photosynthesis in Saline-Alkaline Soils - Zhiming Xie; Ri Song; Hongbo Shao; Fengbin Song; Hongwen Xu; Yan Lu (The Scientific World Journal)
The research aimed to determine the effects of Si application on photosynthetic characteristics of maize on saline-alkaline soil, including photosynthetic rate (Pn), stomatal conductance (gs), transpiration rate (E), and intercellular CO2 concentration (Ci) of maize in the field with five levels (0, 45, 90, 150, and 225 kg·ha−1) of Si supplying. Experimental results showed that the values of Pn, gs, and Ci of maize were significantly enhanced while the values of E of maize were dramatically decreased by certain doses of silicon fertilizers, which meant that Si application with proper doses significantly increased photosynthetic efficiency of maize in different growth stages under stressing environment of saline-alkaline soil. The optimal dose of Si application in this experiment was 150 kg·ha−1 Si. It indicated that increase in maize photosynthesis under saline-alkaline stress took place by Si application with proper doses, which is helpful to improve growth and yield of maize.